Cylindrical foam, and uncrosslinked polyolefin-based resin foam

The production of high-quality cylindrical foams using non-crosslinked polyolefin resin foams with controlled surface roughness and density addresses the challenge of air bubble control, resulting in foams with improved recyclability and insulation properties suitable for diverse applications.

JP2025059598APending Publication Date: 2025-04-10INOAC HOUSING & CONSTR MATERIALS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023169779
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Non-crosslinked resin foams face challenges in controlling air bubbles, particularly when molded into hollow cylindrical shapes for applications requiring specific thickness and insulation properties, leading to reduced quality in the final product.

Method used

A high-quality cylindrical foam is produced using a non-crosslinked polyolefin resin foam with an average surface roughness of 200 μm or less, a density of 15-45 kg/m³, and a thickness of 10-30 mm, utilizing a resin with a breaking tension of 0.13 to 0.30 N at 115°C, and optionally laminated with a skin material.

Benefits of technology

The solution achieves excellent quality cylindrical foams with improved recyclability and enhanced insulation properties, capable of meeting the thickness and shape requirements for various applications while maintaining high tactile feel and surface smoothness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059598000001
    Figure 2025059598000001
Patent Text Reader

Abstract

To provide a cylindrical foam which is applicable to applications required for a specified or more thickness, and has excellent quality regardless of high recyclability.SOLUTION: A cylindrical foam contains an uncrosslinked polyolefin-based resin foam, wherein the average surface roughness of the outer peripheral part according to JIS B0601:1994 in the uncrosslinked polyolefin-based resin foam is 200 μm or less. An uncrosslinked polyolefin-based resin foam has the average surface roughness of the outer peripheral part according to JIS B0601:1994 of 200 μm or less, the density of 15 to 45 kg / m3 and the thickness of 10 to 30 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a cylindrical foam, and more specifically, to a cylindrical foam using a non-crosslinked polyolefin resin foam, and a non-crosslinked polyolefin resin foam. [Background technology]

[0002] In recent years, resin foams have been used in various fields, and the disposal of waste resin foams has become a social issue. In order to contribute to the formation of a sustainable society, attention has been focused on how to utilize waste resin foams as a renewable resource. Resin foams are classified into crosslinked resin foams and non-crosslinked resin foams. Crosslinked resin foams are easy to control the foaming and can form fine bubbles, but they have a problem that they are difficult to recycle because they are crosslinked. On the other hand, non-crosslinked resin foams are easy to recycle because they are not crosslinked, but they have a problem that it is difficult to control the foaming and to obtain a foam with a high expansion ratio.

[0003] For example, Patent Document 1 proposes a technology that uses a polyethylene resin having specific properties to produce an uncrosslinked polyethylene foam molded article made of a polyethylene resin that has a good foaming state (few non-uniform cells or coarse cells, and many uniform cells) while retaining the excellent properties inherent to high-density linear polyethylene, has no thickness unevenness in the foam molded article, has excellent surface properties, and also has a high foaming ratio.

[0004] Patent Document 2 proposes a technique for producing a styrene-based resin foam having a high expansion ratio and a good thickness by extruding the styrene-based resin using carbon dioxide as a foaming agent by using, as a raw material resin, a styrene-based resin whose melt flow rate and melt tension are expressed by a predetermined relationship.

[0005] Incidentally, heat insulating cylinders are used in water supply piping, fireproof water piping, etc. to prevent freezing and burns, and non-crosslinked resin foams are used for these heat insulating cylinders because of their heat insulating properties, shock absorbing properties, and ease of molding. For example, Patent Document 3 proposes a technology for producing an extruded foam for insulation material with low thermal conductivity and little change over time, which has a structure in which a foamed layer (A) is laminated through a non-foamed layer (B) in the thickness direction, and the resin constituting the non-foamed layer (B) contains at least one resin having a lower air permeability than the resin constituting the foamed layer (A).

[0006] The non-crosslinked resin foam can be produced by a chemical foaming method in which foaming is performed by bead foaming or thermal decomposition of a foaming agent, or a physical foaming method in which a resin is kneaded with a liquefied gas or a supercritical fluid to produce foam. For example, the physical foaming method can produce not only a sheet-shaped foam but also a hollow cylindrical foam, which is inexpensive and convenient, and is in high demand as an insulating material or protective material for piping.

[0007] As a technique for producing a hollow cylindrical uncrosslinked resin foam using a physical foaming method, for example, Patent Document 4 proposes a technique for producing a foam having a thickness of 2 mm or more and an apparent density of 90 g / L or less while completely eliminating or barely negligible corrugation, by using a polyolefin resin and adjusting the shape of the foam while cooling the surface immediately after extrusion foaming from a die. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2006-96910 A [Patent Document 2] JP 2000-17097 A [Patent Document 3] JP 2011-173245 A [Patent Document 4] JP 2003-165858 A Summary of the Invention [Problem to be solved by the invention]

[0009] Recently, there is a demand for technologies that can contribute to a decarbonized society, and there is an increasing demand for high-quality resin foams that use as little material as possible. However, as mentioned above, there is a problem with uncrosslinked resin foams, such as the difficulty of controlling bubbles. In particular, when uncrosslinked resin foams are molded into a hollow cylindrical shape for use in heat-insulating tubes for piping and the like, smoothness of the inner diameter and a perfect circular shape are required to protect the piping, and it is also necessary to adjust the thickness to be suitable for heat-insulating and the like. If the thickness is thin, it is possible to make a high-magnification foam by adjusting the amount of gas and molding conditions. On the other hand, in applications where a certain thickness or more is required, there is a problem that it is difficult to control bubbles during foaming, and the quality of the manufactured cylindrical body decreases.

[0010] Therefore, the main objective of this technology is to provide a tubular foam that is applicable to applications requiring a certain level of thickness and has excellent quality while being highly recyclable. [Means for solving the problem]

[0011] Means of the Invention The present inventors have conducted intensive research to solve the above problems and have succeeded in producing a high-quality cylindrical foam using a non-crosslinked polyolefin resin foam, thereby completing the present technology.

[0012] That is, in the present technology, first, a non-crosslinked polyolefin resin foam is provided, In the non-crosslinked polyolefin resin foam, the average surface roughness of the outer periphery in accordance with JIS B0601:1994 is 200 μm or less. A tubular foam is provided. As the raw material of the non-crosslinked polyolefin resin foam used for the cylindrical foam according to the present technology, a resin component having a breaking tension at 115° C. of 0.13 to 0.30 N can be used. A skin material can be laminated on the outer periphery of the tubular foam according to the present technology.

[0013] In this technology, next, the average surface roughness of the outer periphery in accordance with JIS B0601:1994 is 200 μm or less, Density: 15-45kg / m 3 and The thickness is 10 to 30 mm. Provided is a non-crosslinked polyolefin resin foam. The breaking tension of the uncrosslinked polyolefin resin foam according to the present technology at 115° C. can be set to 0.13 to 0.3 N. A skin material can be laminated on at least one surface of the non-crosslinked polyolefin resin foam according to the present technology. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] A preferred embodiment for carrying out the present technology will be described below. The embodiments described below are examples of typical embodiments of the present technology, and any of the embodiments can be combined. In addition, the scope of the present technology is not narrowly interpreted by these.

[0015] 1. Cylindrical foam The cylindrical foam according to the present technology includes a non-crosslinked polyolefin resin foam, and is characterized in that the non-crosslinked polyolefin resin foam has an average surface roughness of 200 μm or less at the outer periphery in accordance with JIS B0601:1994. That is, the cylindrical foam according to the present technology can be produced by molding the non-crosslinked polyolefin resin foam into a cylindrical shape having an average surface roughness of 200 μm or less at the outer periphery. In addition, the cylindrical foam according to the present technology can be provided with a skin material or other members as necessary. The following will explain in detail.

[0016] (1) Non-crosslinked polyolefin resin foam The non-crosslinked polyolefin resin foam is a foam of a resin composition containing a polyolefin resin, a foaming agent, and, if necessary, a shrinkage inhibitor, a bubble adjuster, etc. In addition, various components that can be used for producing the non-crosslinked polyolefin resin foam can be contained depending on the purpose. Each component will be described in detail below.

[0017] (1-1) Polyolefin resin The polyolefin resin that can be used in the non-crosslinked polyolefin resin foam according to the present technology is a resin mainly composed of an olefin component unit. A resin mainly composed of an olefin component unit is a resin containing 50% by mass or more of an olefin component unit. In the present technology, the content of the olefin component unit in the resin is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and it is particularly preferable that the resin component is composed only of a polyolefin resin.

[0018] Examples of polyolefin-based resins that can be used in the present technology include polyethylene-based resins, polypropylene-based resins, polybutene, polypentene, and copolymers of olefin-based monomers and monomers that can be copolymerized with the olefin-based monomers. These can be used alone or in combination of two or more kinds.

[0019] Examples of polyethylene resins include ethylene homopolymers such as high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and very low density polyethylene (VLDPE); ethylene-propylene random copolymers, ethylene-propylene block copolymers, ethylene-butene block copolymers, ethylene-butene random copolymers, ethylene-vinyl acetate copolymers, and ethylene-methyl methacrylate copolymers.

[0020] Examples of polypropylene-based resins include propylene homopolymers such as isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene; propylene-ethylene random copolymers, propylene-ethylene block copolymers, propylene-butene random copolymers, propylene-butene block copolymers, propylene-ethylene-butene terpolymers, propylene-acrylic acid copolymers, and propylene-maleic anhydride copolymers.

[0021] Among these, in the present technology, it is preferable to use a polyethylene-based resin, and among the polyethylene-based resins, it is preferable to use low-density polyethylene (LDPE).

[0022] In addition, in the present technology, a biomass-derived polyolefin resin can be used as a part or the whole of the polyolefin resin. In the present technology, the biomass-derived polyolefin resin refers to a renewable polyolefin resin made from animals and plants, excluding fossil fuels such as petroleum.

[0023] The biomass-derived polyolefin resin that can be used in the present technology can be one or more biomass-derived polyolefin resins produced using a general method, and can be used in any combination, as long as the action and effect of the present technology are not impaired. As an example of a method for producing a biomass-derived polyolefin resin, for example, a method for polymerizing a hydrocarbon such as ethylene derived from biomass can be used to produce a biomass-derived polyolefin resin. The biomass-derived hydrocarbon can be produced using an alcohol such as ethanol derived from biomass as a raw material. The method for producing the biomass-derived alcohol is not particularly limited, and for example, a biomass-derived alcohol can be produced by contacting an alcohol-producing microorganism or a product derived from its crushed material with a culture solution containing a carbon source obtained from a plant raw material such as corn, sugar cane, beet, or manioc, and then purifying the product.

[0024] The polyolefin resin used in the present technology may contain recycled polyolefin resins that are recycled from the waste polyolefin resins described above. In the present technology, the recycled polyolefin resin is a resin produced from a resin composition that has been defoamed and decrosslinked using a general method. That is, in the present technology, the recycled polyolefin resin is not a resin pulverized product obtained by simply pulverizing a resin foam or resin, but a resin that has been defoamed and decrosslinked by subjecting a used polyolefin resin foam to pulverization, shearing, melt kneading, or the like.

[0025] The method for degassing and decrosslinking the used polyolefin resin foam is not particularly limited as long as it does not impair the effects of the present technology, and any general degassing and decrosslinking method can be freely selected and used.

[0026] In addition, the non-crosslinked polyolefin resin foam according to the present technology may contain other resins, thermoplastic elastomers, thermosetting elastomers, etc., in addition to the polyolefin resin, as long as the purpose and effect of the present technology are not impaired. Examples of resins other than polyolefin resins include thermoplastic resins such as polystyrene resins, polyamide resins, and polyester resins. Examples of thermoplastic elastomers include olefin-based thermoplastic elastomers and styrene-based thermoplastic elastomers. Examples of thermosetting elastomers include synthetic rubbers such as ethylene propylene rubber (EPDM) and natural rubber.

[0027] In the present technology, the breaking tension of the resin component used at 115° C. is preferably 0.13 N or more, more preferably 0.15 N or more, even more preferably 0.16 N or more, even more preferably 0.17 or more, and particularly preferably 0.18 N or more. By using a resin having a breaking tension at 115° C. in this range, a foam having a lower density can be produced. In other words, by using a resin having a breaking tension at 115° C. in this range, the expansion rate of the foam can be improved.

[0028] In addition, in the present technology, the breaking tension of the resin component at 115° C. is preferably 0.30 N or less, more preferably 0.28 N or less, even more preferably 0.27 N or less, even more preferably 0.26 N or less, and particularly preferably 0.25 N or less. By using a resin whose breaking tension at 115° C. is in this range, it is possible to suppress formation defects due to excessive foaming.

[0029] In this technology, the breaking tension of the resin component at 115° C. is a value measured by the method described in the examples below.

[0030] (1-2) Foaming agent The resin composition for producing the non-crosslinked polyolefin resin foam according to the present technology may contain a foaming agent. As the foaming agent that can be used in the present technology, one or more foaming agents that can be used in the non-crosslinked polyolefin resin foam may be freely selected and used as long as the purpose and effect of the present technology are not impaired.

[0031] In this technology, both physical and chemical foaming agents can be used, but it is preferable to use a physical foaming agent. In chemical foaming, which is foamed by thermal decomposition or reaction of a chemical foaming agent, decomposition residues of the chemical foaming agent may be generated. On the other hand, physical foaming using a physical foaming agent allows continuous production of non-crosslinked resin foam and does not fall off or leave decomposition residues, so it can be suitably used as an insulating material or protective material for metal pipes where corrosion due to residues is a concern.

[0032] Examples of physical foaming agents include inorganic physical foaming agents and organic physical foaming agents, and either of them can be used in the present technology.

[0033] Examples of inorganic physical blowing agents include nitrogen, carbon dioxide, oxygen, air, water, etc. Examples of organic physical blowing agents include aliphatic hydrocarbons such as isobutane, propane, normal butane, normal pentane, isopentane, normal hexane, and isohexane, alicyclic hydrocarbons such as cyclopentane and cyclohexane, chlorinated hydrocarbons such as methyl chloride and ethyl chloride, fluorinated hydrocarbons such as 1,1,1,2-tetrafluoroethane and 1,1-difluoroethane, ethers such as dimethyl ether and methyl ethyl ether, and alcohols such as methanol and ethanol. In the present technology, it is preferable to use isobutane among these.

[0034] Examples of chemical foaming agents include organic chemical foaming agents and inorganic chemical foaming agents, and either of them can be used in the present technology.

[0035] Examples of organic chemical foaming agents include azo compounds such as azodicarbonamide (ADCA), metal azodicarboxylates (e.g., barium azodicarboxylate), and azobisisobutyronitrile (AIBN), nitroso compounds such as N,N'-dinitrosopentamethylenetetramine (DPT), hydrazine derivatives such as hydrazodicarbonamide, 4,4'-oxybis(benzenesulfonylhydrazide), and toluenesulfonylhydrazide (TSH), and semicarbazide compounds such as toluenesulfonylsemicarbazide.

[0036] Examples of inorganic chemical foaming agents include ammonium carbonate, sodium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and anhydrous monosodium citrate.

[0037] The amount of the foaming agent used in the production of the non-crosslinked polyolefin resin foam according to the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. When a physical foaming agent is used, in the present technology, the lower limit of the amount of the foaming agent used relative to 100 parts by mass of the resin component in the resin composition is, for example, 0.05 L / min or more, preferably 0.10 L / min or more, and more preferably 0.15 L / min or more. By setting the amount of the foaming agent used within this range, the foamability during foam production can be improved, and the physical properties of the foam produced can be improved.

[0038] In the present technology, the upper limit of the amount of foaming agent used per 100 parts by mass of the resin component in the resin composition is, for example, 0.50 L / min or less, preferably 0.40 L / min or less, and more preferably 0.35 L / min or less. By setting the amount of foaming agent used in the resin composition within this range, formation defects due to excessive foaming can be suppressed, and also cost reduction can be contributed.

[0039] (1-3) Shrinkage prevention agent The resin composition for producing the non-crosslinked polyolefin resin foam according to the present technology may contain a shrinkage inhibitor.

[0040] As the shrinkage prevention agent that can be used in the present technology, one or more shrinkage prevention agents that can be used for non-crosslinked polyolefin resin foams can be freely selected and used, as long as the purpose and effect of the present technology are not impaired.

[0041] Examples of shrinkage inhibitors that can be used in the present technology include ester-based shrinkage inhibitors such as glycerin fatty acid esters such as monolauric acid glyceride, monomyristate acid glyceride, monopalmitic acid glyceride, monostearate acid glyceride, monoarachic acid glyceride, dilauric acid glyceride, dipalmitic acid glyceride, distearate acid glyceride, 1-palmito-2-stearate acid glyceride, 1-stearo-2-myristate acid glyceride, and tristearate acid glyceride; polyoxyalkylene fatty acid esters such as polyoxyethylene monomyristate, polyoxypropylene monomyristate, polyoxyethylene monopalmitate, polyoxypropylene monopalmitate, polyoxyethylene monostearate, polyoxypropylene monostearate, and polyoxyethylene distearate; and amine- and amide-based shrinkage inhibitors such as stearic acid amide, palmitic acid amide, stearic acid diethanolamide, stearic acid monoethanolamide, hydroxyethylamine, and hydroxypropylamine.

[0042] Among these, in the present technology, it is preferable to use an ester-based shrinkage inhibitor, and it is more preferable to use a glycerin fatty acid ester.

[0043] The amount of shrinkage inhibitor used in the production of the non-crosslinked polyolefin resin foam according to the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the shrinkage inhibitor relative to 100 parts by mass of the resin component in the resin composition is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and more preferably 1.0 parts by mass or more. By setting the content of the shrinkage inhibitor in the resin composition within this range, the shrinkage of the foam can be more effectively suppressed.

[0044] In the present technology, the upper limit of the content of the shrinkage inhibitor relative to 100 parts by mass of the resin component in the resin composition is, for example, 15.0 parts by mass or less, preferably 10.0 parts by mass or less, and more preferably 5.0 parts by mass or less. By setting the content of the shrinkage inhibitor in the resin composition within this range, it is possible to suppress the exudation of the shrinkage inhibitor to the surface of the foam and also to contribute to cost reduction.

[0045] In the present technology, the shrinkage inhibitor can be used as a masterbatch in which the shrinkage inhibitor is dispersed in the resin component. By using the shrinkage inhibitor masterbatch, the dispersibility in the resin component can be improved.

[0046] (1-4) Foam regulator The resin composition for producing the non-crosslinked polyolefin resin foam according to the present technology may contain a cell regulator.

[0047] As the cell regulator that can be used in the present technology, one or more cell regulators that can be used in non-crosslinked polyolefin resin foams can be freely selected and used, as long as they do not impair the purpose and effect of the present technology.

[0048] Examples of the foam regulator that can be used in the present technology include inorganic foam regulators such as talc, zeolite, silica, calcium carbonate, zinc borate, magnesium borate, borax and other metal borates, sodium chloride, aluminum hydroxide, sodium bicarbonate, etc.; and organic foam regulators such as sodium 2,2-methylenebis(4,6-tert-butylphenyl)phosphate, sodium benzoate, calcium benzoate, aluminum benzoate, sodium stearate, etc.

[0049] Among these, in the present technology, it is preferable to use an inorganic cell regulator, and it is more preferable to use talc.

[0050] The amount of the cell regulator used in the production of the non-crosslinked polyolefin resin foam according to the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the content of the cell regulator relative to 100 parts by mass of the resin component in the resin composition is, for example, 0.05 parts by mass or more, preferably 0.1 parts by mass or more, and more preferably 0.5 parts by mass or more. By setting the content of the cell regulator in the resin composition within this range, the shrinkage of the foam can be more effectively suppressed.

[0051] In the present technology, the upper limit of the content of the cell regulator per 100 parts by mass of the resin component in the resin composition is, for example, 10.0 parts by mass or less, preferably 7.0 parts by mass or less, and more preferably 4.0 parts by mass or less. By setting the content of the cell regulator in the resin composition within this range, it is also possible to contribute to cost reduction.

[0052] In the present technology, the cell regulator can be used as a master batch in which the cell regulator is dispersed in the resin component. By using the cell regulator master batch, the dispersibility in the resin component can be improved.

[0053] (1-5) Other ingredients In the production of the non-crosslinked polyolefin resin foam according to the present technology, one or more of various components that can be used in the production of non-crosslinked polyolefin resin foam can be freely selected and used as other components depending on the purpose, as long as the purpose and effects of the present technology are not impaired.

[0054] Examples of components that can be used in the production of the non-crosslinked polyolefin resin foam according to the present technology include foaming assistants, inorganic fillers, foam stabilizers, lubricants, flame retardants, stabilizers, plasticizers, colorants, antioxidants, dispersants, and ultraviolet absorbers.

[0055] (1-6) Average surface roughness of outer periphery In the cylindrical foam according to the present technology, the average surface roughness of the outer periphery of the non-crosslinked polyolefin resin foam is 200 μm or less. By making the average surface roughness of the outer periphery of the non-crosslinked polyolefin resin foam 200 μm or less, not only is the appearance of the cylindrical foam improved, but also, when a skin material is laminated as described below, the workability of the skin material lamination step is improved and peeling between the non-crosslinked polyolefin resin foam and the skin material can be prevented.

[0056] The average surface roughness of the outer periphery of the uncrosslinked polyolefin resin foam can exert the functions and effects of the present technology so long as it is 200 μm or less, but is preferably 180 μm or less, more preferably 170 μm or less, even more preferably 160 μm or less, still more preferably 150 μm or less, and particularly preferably 140 μm or less.

[0057] The lower limit of the average surface roughness of the peripheral portion of the non-crosslinked polyolefin resin foam is not particularly limited, but is, for example, 30 μm or more, preferably 50 μm or more, more preferably 60 μm or more, even more preferably 80 μm or more, still more preferably 100 μm or more, and particularly preferably 110 μm or more. By setting the lower limit of the average surface roughness of the peripheral portion of the non-crosslinked polyolefin resin foam within this range, a foam with a lower density can be obtained.

[0058] In the present technology, the average surface roughness of the outer periphery of the non-crosslinked polyolefin resin foam is a value measured in accordance with JIS B0601:1994.

[0059] (1-7) Density In the cylindrical foam according to the present technology, the density of the non-crosslinked polyolefin resin foam can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the density of the non-crosslinked polyolefin resin foam is, for example, 10 kg / m 3 More than 13kg / m 3 More preferably, 17 kg / m 3 More preferably, 20 kg / m 3By setting the lower limit of the density of the non-crosslinked polyolefin resin foam in this range, it is possible to prevent the foam from becoming too soft and to impart appropriate elasticity to the foam.

[0060] The upper limit of the density of the non-crosslinked polyolefin resin foam used in this technology is, for example, 50 kg / m 3 Less than 40 kg / m 3 Less than or equal to 35 kg / m 3 By setting the density of the non-crosslinked polyolefin resin foam within this range, the non-crosslinked polyolefin resin foam can be prevented from becoming too hard and losing flexibility, and can be provided with appropriate cushioning properties. In addition, the insulation properties and heat retention properties can be improved.

[0061] In the present technology, the density of the polyolefin resin foam is a value measured in accordance with a method based on JIS K7222.

[0062] (1-8) Inner diameter The cylindrical foam according to the present technology can be obtained by molding a non-crosslinked polyolefin resin foam into a cylindrical shape, and the inner diameter can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the inner diameter of the cylindrical non-crosslinked polyolefin resin foam is, for example, 10 mm or more, preferably 13 mm or more, more preferably 14 mm or more, and even more preferably 15 mm or more. By setting the lower limit of the inner diameter of the cylindrical non-crosslinked polyolefin resin foam in this range, the moldability can be improved.

[0063] The upper limit of the inner diameter of the cylindrical non-crosslinked polyolefin resin foam is, for example, 80 mm or less, preferably 70 mm or less, and more preferably 65 mm or less. By setting the inner diameter of the cylindrical non-crosslinked polyolefin resin foam within this range, the cylindrical body can have an appropriate thickness, and the insulation and heat retention can be improved.

[0064] (1-9) Outer diameter In addition, the outer diameter of the cylindrical non-crosslinked polyolefin resin foam can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the outer diameter of the cylindrical non-crosslinked polyolefin resin foam is, for example, 30 mm or more, preferably 35 mm or more, more preferably 45 mm or more, and even more preferably 50 mm or more. By setting the lower limit of the outer diameter of the cylindrical non-crosslinked polyolefin resin foam in this range, the cylindrical body can have an appropriate thickness, and the insulation property and heat retention property can be improved.

[0065] The upper limit of the outer diameter of the cylindrical non-crosslinked polyolefin resin foam is, for example, 100 mm or less, preferably 90 mm or less, and more preferably 80 mm or less. By setting the outer diameter of the cylindrical non-crosslinked polyolefin resin foam in this range, moldability can be improved.

[0066] (1-10) Thickness The thickness of the non-crosslinked polyolefin resin foam used in the present technology can be freely set as long as it does not impair the purpose and effect of the present technology. In the present technology, the lower limit of the thickness of the non-crosslinked polyolefin resin foam is, for example, 5 mm or more, preferably 7 mm or more, more preferably 8 mm or more, and even more preferably 10 mm or more. By setting the lower limit of the thickness of the non-crosslinked polyolefin resin foam within this range, the insulation property and heat retention property can be improved.

[0067] The upper limit of the thickness of the non-crosslinked polyolefin resin foam is, for example, 50 mm or less, preferably 40 mm or less, and more preferably 30 mm or less. By setting the thickness of the non-crosslinked polyolefin resin foam in this range, moldability can be improved.

[0068] (1-11) Breaking tension of remelt at 115℃ The non-crosslinked polyolefin resin foam used in the present technology is pulverized and remelted, and the remelted product has a breaking tension at 115° C. of preferably 0.09 N or more, more preferably 0.10 N or more, even more preferably 0.13 N or more, even more preferably 0.15 N or more, and particularly preferably 0.16 N or more. When the breaking tension at 115° C. of the remelted product is within this range, a foam having a lower density can be obtained.

[0069] In addition, in the present technology, the breaking tension of the remelt at 115° C. is preferably 0.28 N or less, more preferably 0.26 N or less, even more preferably 0.25 N or less, even more preferably 0.24 N or less, and particularly preferably 0.23 N or less. When the breaking tension of the remelt at 115° C. is within this range, a foam with good moldability can be obtained.

[0070] In this technique, the breaking tension of the remelted material at 115° C. is also a value measured by the method described in the examples below.

[0071] (2)Skin material A skin material can be laminated on the non-crosslinked polyolefin resin foam according to the present technology. When the non-crosslinked polyolefin resin foam is molded into a cylindrical shape, a skin material can be laminated on the outer periphery of the cylindrical foam, and when the non-crosslinked polyolefin resin foam is molded into a sheet or plate shape, a skin material can be laminated on one or more surfaces.

[0072] The material used for the skin is not particularly limited, and one or a combination of two or more types of skin materials can be used depending on the application and purpose, such as resin, metal, woven fabric, nonwoven fabric, foam, etc. In addition, it is also possible to laminate two or more layers of skin materials made of the same material or different materials.

[0073] The skin material and the non-crosslinked polyolefin resin foam are preferably bonded together. As the bonding method, one or more methods generally used for bonding a skin material and a non-crosslinked polyolefin resin foam may be freely combined and used, as long as the function and effect of the present technology are not impaired.

[0074] Examples of such methods include a method of adhering a sheet-like skin material to a non-crosslinked polyolefin resin foam using an adhesive, a method of heating and melting the surface of a sheet-like skin material and / or the surface of a non-crosslinked polyolefin resin foam to thermally fuse the material, a method of laminating a molten skin material onto the surface of a non-crosslinked polyolefin resin foam by a method such as extrusion molding, a method of integrally molding a non-crosslinked polyolefin resin foam onto the hollow portion of a cylindrically molded skin material or the surface of a sheet-shaped skin material to adhere the material, etc. Among these, in the present technology, it is preferable to select a method of laminating a molten skin material onto the surface of a non-crosslinked polyolefin resin foam by a method such as extrusion molding to adhere the material.

[0075] The skin material preferably has a dynamic friction coefficient of 0.50 or less, more preferably 0.45 or less, even more preferably 0.42 or less, and still more preferably 0.40 or less, in accordance with JIS K7125. By setting the upper limit of the dynamic friction coefficient of the skin material within this range, the peel strength between the skin material and the non-crosslinked polyolefin resin foam can be further improved.

[0076] The lower limit of the dynamic friction coefficient of the covering material according to the present technology can be freely set as long as it does not impair the purpose and effect of the present technology, and can be set to, for example, 0.05 or more.

[0077] In this technology, the dynamic friction coefficient of the skin material is a value measured in accordance with JIS K7125.

[0078] The thickness of the skin material can be freely designed according to the purpose and use, but with this technology it can be designed to be, for example, 0.6 mm or less, and even 0.5 mm or less. By reducing the thickness, the amount of material used can be reduced, which reduces costs, simplifies waste disposal, and also contributes to the environment.

[0079] In this technology, the thickness of the skin material is the average value of thicknesses measured at six points with a micrometer.

[0080] When a skin material is laminated on the non-crosslinked polyolefin resin foam according to the present technology, the average surface roughness of the skin material is not limited as long as it does not impair the function and effect of the present technology, but is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. By setting the upper limit of the average surface roughness of the skin material within this range, not only can the appearance of the skin material be improved, but peeling between the non-crosslinked polyolefin resin foam and the skin material can be prevented.

[0081] The lower limit of the average surface roughness of the skin material is not particularly limited, but can be, for example, 1 μm or more.

[0082] In this technology, the average surface roughness of the skin material is a value measured in accordance with JIS B0601:1994.

[0083] When a skin material is laminated on the non-crosslinked polyolefin resin foam according to the present technology, the thickness shrinkage rate of the laminate is not limited as long as it does not impair the action and effect of the present technology, but is preferably 7% or less, more preferably 5% or less, and even more preferably 4% or less. When the upper limit of the thickness shrinkage rate of the laminate is within this range, deterioration of the quality of the laminate due to changes in the surrounding environment such as temperature changes can be prevented.

[0084] The lower limit of the thickness shrinkage rate of the laminate is not particularly limited, and the closer it is to 0, the more the laminate can be prevented from suffering deterioration in quality due to changes in the surrounding environment, such as temperature changes.

[0085] In this technology, the thickness shrinkage rate of the laminate is a value measured in accordance with JIS A9511 after heating the skin portion of the laminate at 70°C for 168 hours and then curing it for 24 hours.

[0086] When a skin material is laminated onto the non-crosslinked polyolefin resin foam according to the present technology, the peel strength between the non-crosslinked polyolefin resin foam and the skin material is not particularly limited as long as it does not impair the action and effect of the present technology, but is preferably 1.5 N / 20 mm or more, more preferably 1.7 N / 20 mm or more, and even more preferably 2.0 N / 20 mm or more. If the peel strength is within this range, peeling of the surface material during use can be prevented in various applications.

[0087] The upper limit of the peel strength between the non-crosslinked polyolefin resin foam and the skin material is not particularly limited as long as it does not impair the action and effect of the present technology, but can be, for example, 10 N / 20 mm or less. By setting the upper limit of the peel strength between the non-crosslinked polyolefin resin foam and the skin material within this range, it is possible to facilitate separation of the non-crosslinked polyolefin resin foam and the skin material when recycling the non-crosslinked polyolefin resin foam.

[0088] In the present technology, the peel strength between the non-crosslinked polyolefin resin foam and the skin material is a value measured by the method described in the examples below.

[0089] The skin material used in the present technology is disposed on the outermost surface of the essential structure of the molded product using the non-crosslinked polyolefin resin foam to which the skin material is adhered, and therefore the term "skin" is used for convenience, but in an actual product, it is not limited to being disposed on the outermost surface. For example, it is also possible to further laminate a desired material on the surface of the skin material, to cover the skin material with a desired material, or to cover the entire molded product with a desired material.

[0090] 2. Manufacturing method of cylindrical foam and non-crosslinked polyolefin resin foam The cylindrical foam using the non-crosslinked polyolefin resin foam according to the present technology has characteristic physical properties, and the manufacturing method thereof is not particularly limited as long as it does not impair the action and effect of the present technology. The non-crosslinked polyolefin resin foam can be manufactured by freely combining one or more of the general manufacturing methods for non-crosslinked polyolefin resin foam.

[0091] In this technology, it is preferable to perform extrusion molding. Specifically, for example, a raw material polyolefin resin and, if necessary, additives such as a shrinkage inhibitor and a bubble adjuster are fed to an extruder and mixed under heat, and then a foaming agent is pressed in and further kneaded to prepare a foamable molten resin composition. The prepared foamable molten resin composition is introduced into an annular die provided downstream of the extruder, and extruded from the tip of the annular die into the atmosphere to foam, thereby producing a cylindrical foam.

[0092] When producing a non-crosslinked polyolefin resin foam in a shape other than a cylinder (for example, in a sheet or plate shape), a foam in the desired shape can be produced by designing the shape of the die downstream of the extruder according to the purpose.

[0093] When a skin material is laminated on the outer periphery of a cylindrical uncrosslinked polyolefin resin foam or on at least one surface of a sheet-like or plate-like uncrosslinked polyolefin resin foam, one or more general methods for laminating a skin material on the surface of a resin foam can be freely combined, as long as the lamination method does not impair the action and effect of the present technology.

[0094] Examples of such methods include a method of laminating a sheet-like skin material onto a non-crosslinked polyolefin resin foam using an adhesive, a method of heating and melting the surface of a sheet-like skin material and / or the surface of a non-crosslinked polyolefin resin foam to heat-fuse, a method of laminating a molten skin material onto the surface of a non-crosslinked polyolefin resin foam by a method such as extrusion molding, a method of integrally molding a non-crosslinked polyolefin resin foam onto a hollow portion of a cylindrically molded skin material or onto the surface of a sheet-shaped skin material, etc. Among these, in the present technology, it is preferable to laminate a skin material onto a non-crosslinked polyolefin resin foam by a method such as extrusion molding.

[0095] 3. Applications of cylindrical foams and non-crosslinked polyolefin resin foams The cylindrical foam and the non-crosslinked polyolefin resin foam according to the present technology can be used for various applications in various fields by utilizing their high quality. For example, they can be suitably used as pipe insulation materials, building shock-absorbing materials, building insulation materials, building soundproofing materials, packaging materials, vehicle shock-absorbing materials, building interior materials, vehicle interior materials, etc. Among these, the cylindrical foam and the non-crosslinked polyolefin resin foam according to the present technology can be suitably used for heat insulation applications, particularly as pipe insulation materials. EXAMPLES

[0096] The present technology will be described in more detail below based on examples. Note that the examples described below are representative examples of the present technology, and the scope of the present technology is not to be interpreted narrowly by these examples.

[0097] (1) Raw materials Polyolefin resin 1: Low-density polyethylene (LDPE) (MFR: 1g / 10min, melting point: 108℃) Polyolefin resin 2: Low-density polyethylene (LDPE) (MFR: 2.7 g / 10 min, melting point: 110°C, Braskem SA "LDPE SEB853" (biomass LDPE derived from sugar cane)) Polyolefin resin 3: Low-density polyethylene (LDPE) (MFR: 1g / 10min, melting point: 110℃) Polyolefin resin 4: Low-density polyethylene (LDPE) (MFR: 2g / 10min, melting point: 110℃) Polyolefin resin 5: Low density polyethylene (LDPE) (MFR: 1.2g / 10min, melting point: 120℃) Shrinkage inhibitor (shrinkage inhibitor masterbatch): Eiwa Chemical Industry Co., Ltd. "Polyslen EE15Z" (masterbatch of glycerin fatty acid ester and polyolefin resin 6 (low density polyethylene (LDPE)). In Table 1, the calculation is based on glycerin fatty acid ester: polyolefin resin 6 = 50%:50%). Air bubble regulator (air bubble regulator masterbatch): Masterbatch of 43% talc and 57% polyolefin resin 7 (polyethylene (PE))

[0098] (2) Manufacturing of cylindrical foam The raw materials shown in Table 1 below were fed to an extruder, heated and kneaded, and further isobutane was added as a physical foaming agent and kneaded to prepare a foamable molten resin composition. The foamable molten resin composition thus prepared was introduced into an annular die provided downstream of the extruder, and extruded from the lip at the end of the annular die into the atmosphere to cause foaming, producing a cylindrical foam.

[0099] (3) Measurement and evaluation of physical properties The breaking tension at 115° C. of the raw material polyolefin resin component, and the average surface roughness, density and feel of the outer periphery of the produced cylindrical foam were measured or evaluated by the following methods.

[0100] [Breaking tension at 115℃] The breaking tension at 115°C was measured using a capillograph. Specifically, the raw resin was discharged from a capillary with a diameter of 1.00 mm and a length of 10.0 mm in a temperature environment set at 115°C at a shear rate of 10 M / min, and the discharged molten resin (strand) was taken up by a take-up roller via a pulley-shaped load cell. The speed of the take-up roller was accelerated, and the breaking tension (N) at the time of the strand breaking was measured.

[0101] The produced cylindrical foam was crushed and remelted, and the breaking tension of the remelted product at 115° C. was also measured in the same manner.

[0102] [Average surface roughness of outer periphery] The average surface roughness of the outer periphery was measured in accordance with JIS B0601:1994.

[0103] [density] The density was measured in accordance with JIS K7222.

[0104] [Touch] Five panelists evaluated the texture according to the following criteria. If even one of the five panelists rated the product as "x", the product was marked as "x". 〇: No problems with surface unevenness when laminating the skin material ×: Defects in surface unevenness when laminating the skin material

[0105] (4) Results The results are shown in Table 1 below. [Table 1]

[0106] (5) Discussion As shown in Table 1, in Examples 1 to 5 in which the average surface roughness of the outer periphery is 200 μm or less, there is no problem with the surface unevenness when laminating the skin material, and the skin material has an excellent touch. In addition, in Comparative Example 3 in which the breaking tension of the raw material resin at 115° C. exceeds 0.30 N, foaming was not possible. Although foaming is possible by devising other raw materials, it was found that in order to obtain a good foam with less raw materials, the breaking tension of the raw material resin at 115° C. is preferably 0.30 N or less. In other words, by making the breaking tension of the raw material resin at 115° C. 0.30 N or less, the recyclability of the cylindrical foam can be improved.

[0107] Comparing the examples, Example 5, in which the breaking tension of the raw resin at 115°C was less than 0.15N, had a higher density than the other examples. It was found that in order to produce a low-density cylindrical foam, the breaking tension of the raw resin at 115°C is preferably 0.15N or more. It was possible to reduce the density by reducing the thickness as in Example 4. In other words, when increasing the thickness while maintaining a low average surface roughness of the outer periphery (Example 5), it was necessary to reduce the amount of gas (amount of foaming agent) to increase the density. When the density was reduced, the average surface roughness of the outer periphery increased as in Comparative Example 1, resulting in a reduced tactile feel.

Claims

1. Non-crosslinked polyolefin resin foam, In the non-crosslinked polyolefin resin foam, the average surface roughness of the outer periphery in accordance with JIS B0601:1994 is 200 μm or less. Cylindrical foam.

2. 2. The cylindrical foam according to claim 1, wherein the resin component serving as a raw material for the non-crosslinked polyolefin resin foam has a breaking tension at 115° C. of 0.13 to 0.30 N.

3. The cylindrical foam according to claim 1 or 2, further comprising a skin material laminated on the outer periphery.

4. The average surface roughness of the outer periphery in accordance with JIS B0601:1994 is 200 μm or less, Density: 15-45kg / m 3 and The thickness is 10 to 30 mm. Non-crosslinked polyolefin resin foam.

5. The non-crosslinked polyolefin resin foam according to claim 4, having a breaking tension at 115°C of 0.13 to 0.3 N.

6. The non-crosslinked polyolefin resin foam according to claim 4 or 5, which has a skin material laminated on at least one surface thereof.

Citation Information

Patent Citations

  • Styrenic resin foam and its preparation

    JP2000017097A

  • Extruded foam of polyolefin resin

    JP2003165858A

  • Uncross-linked polyethylene expansion molded product

    JP2006096910A

  • Extruded foam superior in insulating performance

    JP2011173245A